2002
DOI: 10.1128/iai.70.3.1235-1244.2002
|View full text |Cite
|
Sign up to set email alerts
|

RecombinantDirofilaria immitisPolyprotein That Stimulates Murine B Cells To Produce Nonspecific Polyclonal Immunoglobulin E Antibody

Abstract: Nonspecific immunoglobulin E (IgE) production is an event characteristically observed in parasitic helminth infections, but its mechanisms are still unclear. To define these mechanisms, we prepared a recombinant Dirofilaria immitis protein (rDiAg) and assessed its effect on nonspecific IgE production. rDiAg preferentially induced nonspecific IgE production, without eliciting specific IgE production, as well as a Th2-type cytokine profile (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 51 publications
(63 reference statements)
0
29
0
Order By: Relevance
“…NPAs are predominantly located in the pseudocoelomic fluid of ascarids (including the porcine intestinal roundworm Ascaris suum) or on the surface of filariae (including the canine heartworm Dirofilaria immitis) and are secreted as a major component of the excretory-secretory (ES) product (7). More recently, we have found that the D. immitis polyprotein (DiAg; a Dirofilaria NPA) can bind to human CD40 molecules and induces antigen-nonspecific polyclonal immunoglobulin E (IgE) production by highly purified human and murine B cells in the presence of interleukin-4 (6,19). To verify that DiAg signaling occurs via CD40, we examined the effect of DiAg on NO synthesis by CD40-bearing and CD40-defective macrophages.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…NPAs are predominantly located in the pseudocoelomic fluid of ascarids (including the porcine intestinal roundworm Ascaris suum) or on the surface of filariae (including the canine heartworm Dirofilaria immitis) and are secreted as a major component of the excretory-secretory (ES) product (7). More recently, we have found that the D. immitis polyprotein (DiAg; a Dirofilaria NPA) can bind to human CD40 molecules and induces antigen-nonspecific polyclonal immunoglobulin E (IgE) production by highly purified human and murine B cells in the presence of interleukin-4 (6,19). To verify that DiAg signaling occurs via CD40, we examined the effect of DiAg on NO synthesis by CD40-bearing and CD40-defective macrophages.…”
mentioning
confidence: 99%
“…rDiAg was prepared with Escherichia coli as described previously (19). The recombinant protein was then passed through a column of polymyxin B-immobilized beads and found to have negligible endotoxin levels (Ͻ2 pg of LPS/mg of protein) as measured by Endotoxin Test-D (Seikagaku, Tokyo, Japan) (19).…”
mentioning
confidence: 99%
See 3 more Smart Citations